2018
DOI: 10.1002/gj.3311
|View full text |Cite
|
Sign up to set email alerts
|

Cambrian magmatism in the Tethys Himalaya and implications for the evolution of the Proto‐Tethys along the northern Gondwana margin: A case study and overview

Abstract: The Cuonadong Dome in southern Tibet is a newly discovered gneiss dome in the Tethys Himalaya. Here, we investigate the Late Cambrian augen gneiss (orthogneiss) within the core of this dome to address the controversy surrounding early Palaeozoic tectonic evolution of the northern margin of eastern Gondwana. We report new zircon laser ablation multicollector inductively coupled plasma mass spectrometry (LA‐(MC‐)ICP‐MS) U‐Pb ages, Lu‐Hf isotopes, whole‐rock major and trace element geochemistry, and Sr‐Nd‐Pb data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 166 publications
(303 reference statements)
0
5
0
Order By: Relevance
“…Tectonic map of the Himalaya–Tibetan Plateau region: (a) geotectonic sketch of southeastern Asia (Cao et al, ; Yin & Harrison, ); (b) simplified geological map of Himalaya, showing the distribution of leucogranites (modified after Cao et al, ; Guillot et al, ; Zhang et al, ). Age of Dajia granites is from Wang et al (); age of the Langshan gabbros is from Ji et al (); age of the Napuri adakitic rocks is from Ma et al () [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Geological Background and Sample Descriptionsmentioning
confidence: 99%
“…Tectonic map of the Himalaya–Tibetan Plateau region: (a) geotectonic sketch of southeastern Asia (Cao et al, ; Yin & Harrison, ); (b) simplified geological map of Himalaya, showing the distribution of leucogranites (modified after Cao et al, ; Guillot et al, ; Zhang et al, ). Age of Dajia granites is from Wang et al (); age of the Langshan gabbros is from Ji et al (); age of the Napuri adakitic rocks is from Ma et al () [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Geological Background and Sample Descriptionsmentioning
confidence: 99%
“…The southern margin of Gondwana, spanning approximately 15,000 km, had initiated subduction by 530 Ma, which progressed into the Terra Australis Orogen that peaked around 515 to 500 Ma ( 78 82 ). The margin of northeastern Gondwana was also convergent within this time window, with subduction along the entire margin from Australia to Turkey from 530 to 490 Ma ( 82 85 ). This subduction extended west as part of the Avalonian-Cadomian orogenic arc, essentially along the entire northern margin of Gondwana ( 86 89 ).…”
Section: The Great Unconformity As a Far-field Record Of Hypsometric ...mentioning
confidence: 89%
“…These domes, between the ITSZ and the STDS, all belong to the North Himalayan Gneiss Domes (NHGD; Fu et al, 2020; Langille, Jessup, Cottle, & Ahmad, 2014; Lee, Hacker, & Wang, 2004). Lalong, Qialong, and Cuonadong were newly discovered dome structures in recent years (Huang et al, 2017; Huang, Fu, Li, Zhang, & Liu, 2019; Zhang et al, 2018, 2019). These domes exhibit a similar geologic framework with leucogranites, gneisses, migmatites, and unmetamorphosed sedimentary rocks (Langille et al, 2014; Lee et al, 2004).…”
Section: Geological Settingmentioning
confidence: 99%
“…As one of the regions with the strong metallogenic potential for Cu–Pb–Zn–Au deposits in the Qinghai‐Tibet Plateau, the Tethys Himalaya metallogenic belt is thus considered to be a critical mineral resource enrichment zone. In recent years, Be‐W‐Sn deposits were found in the Cuonadong dome (Fu et al, 2017, 2018a; Li et al, 2017; Zhang et al, 2019). Moreover, mineral exploration further confirmed that this type deposit has a very high exploration potential (Cao et al, 2020; Sun et al, 2018; Xie et al, 2017; Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation